MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIKA DENGAN PENERAPAN STRATEGI RECIPROCAL TEACHING - Kurniasih, Ranti (AlphaMath : Journal of Mathematics Education, 2017)
The ability of mathematical connection is an important thing to be trained to students. Initialobservation when this research was conducted showed that there were problems ofmathematics learning in SMA Al-Muqoddasah of Ponorogo, that is, the tendency of teachercentered learning activities and low learning result of mathematics students especially inrelation between some concepts in mathematics. Reciprocal Teaching Strategy is one of thealternatives that can be done to help students connect some concepts in learning mathematics,and enable students so that they can think creatively and critically. The purpose of this studyis to describe the learning with Reciprocal Teaching strategy that can improve students'mathematical connection ability in SMA Al-Muqoddasah of Ponorogo.Keyword: Mathematical Representation Ability, Reciprocal Teaching.